The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1158/1078-0432.ccr-10-2946
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of GSK461364, a Specific and Competitive Polo-like Kinase 1 Inhibitor, in Patients with Advanced Solid Malignancies

Abstract: Purpose: GSK461364 is an ATP-competitive inhibitor of polo-like kinase 1 (Plk1). A phase I study of two schedules of intravenous GSK461364 was conducted.Experimental Design: GSK461364 was administered in escalating doses to patients with solid malignancies by two schedules, either on days 1, 8, and 15 of 28-day cycles (schedule A) or on days 1, 2, 8, 9, 15, and 16 of 28-day cycles (schedule B). Assessments included pharmacokinetic and pharmacodynamic profiles, as well as marker expression studies in pretreatme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 23 publications
2
108
0
1
Order By: Relevance
“…Future clinical studies should include the detection of pharmacodynamic biomarkers, such as phospho-histone H3, to validate Plk1 as the tumor target. In the first-in-humans phase I study of GSK461364 in advanced solid tumors, Plk1 inhibition in tumor cells was confirmed on the basis of the analysis of phospho-histone H3 expression in circulating tumor cells (59). Other promising biomarker assays for Plk1 inhibition in vivo have been developed, such as an immunohistochemical approach that measures serine 46-phosphorylation of the translational controlled tumor protein by Plk1 (62) and an ELISA-based assay that measures phosphorylation of the PBD-binding protein 1 (PBIP1, also known as MLF1 or CENP-U) by Plk1 (63).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Future clinical studies should include the detection of pharmacodynamic biomarkers, such as phospho-histone H3, to validate Plk1 as the tumor target. In the first-in-humans phase I study of GSK461364 in advanced solid tumors, Plk1 inhibition in tumor cells was confirmed on the basis of the analysis of phospho-histone H3 expression in circulating tumor cells (59). Other promising biomarker assays for Plk1 inhibition in vivo have been developed, such as an immunohistochemical approach that measures serine 46-phosphorylation of the translational controlled tumor protein by Plk1 (62) and an ELISA-based assay that measures phosphorylation of the PBD-binding protein 1 (PBIP1, also known as MLF1 or CENP-U) by Plk1 (63).…”
Section: Discussionmentioning
confidence: 96%
“…The recommended phase II dose for GSK461364 was 225 mg on days 1, 8, and 15 in a 28-day cycle. Because of the high incidence (20%) of venous thromboembolism, GSK461364 should involve coadministration of prophylactic anticoagulation for further clinical evaluation (59).…”
Section: Gsk461364mentioning
confidence: 99%
“…Our study tests the PLK1 small-molecule inhibitor, BI2536, which has been evaluated in patients with cancer (33,34). Various other small molecule inhibitors to PLK1 have been designed and evaluated in phase I/II clinical trials including BI2536, BI6727, Rigosertib, and GSK461364 (35)(36)(37)(38)(39). None of these trials have specifically addressed the possibility that PLK1 inhibitors may be beneficial for the treatment of brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that PLK1 and PLK4 may represent attractive therapeutic targets for this subgroup of breast cancer. We then focused on PLK1 because several PLK1 inhibitors have been evaluated in clinical trials (8,27,34,35).…”
Section: Plk1 Is Overexpressed In Triple-negative Breast Cancermentioning
confidence: 99%